1996
DOI: 10.1093/oxfordjournals.molbev.a025667
|View full text |Cite
|
Sign up to set email alerts
|

The divergent domains of the NEFA and nucleobindin proteins are derived from an EF-hand ancestor

Abstract: The human protein NEFA (DNA binding, EF-hand, Acidic region) has previously been isolated from a KM3 cell line and immunolocalized on the plasma membrane, in the cytoplasma, and in the culture medium. Sequence analysis of a cDNA clone encoding NEFA identified a hydrophilic domain, two EF-hands, and a leucine zipper at the C-terminus. These characters are shared with nucleobindin (Nuc). In this paper we have further characterized NEFA and probed its evolutionary origins. Circular dichroism (CD) spectra of recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…They share 61.65% amino acid identity and a characteristic composition of functional domains -a signal peptide, a Leu/Ile rich region, basic amino acid rich region including putative bipartite nuclear localisation signal, two Ca 2+ binding EF-hand domains separated by acidic amino acid rich region and a leucine zipper (Figure 1) (Barnikol-Watanabe et al 1994;Miura et al 1992). Genes encoding NUCB1 and NUCB2 are located in 19q13.2-q13.4 and 11p15.1-p14, respectively, and are deemed to be derived from a common four-domain EF-hand ancestor (Karabinos et al 1996). Within the cell both are located in the cytoplasmic and Golgi luminal pools, both are secreted into extracellular space and interact with other proteins in a calciumdependent manner (Lavoie et al 2002;Lin et al 2000;Morel-Huaux et al 2002;Taniguchi et al 2000;Islam et al 2006).…”
mentioning
confidence: 99%
“…They share 61.65% amino acid identity and a characteristic composition of functional domains -a signal peptide, a Leu/Ile rich region, basic amino acid rich region including putative bipartite nuclear localisation signal, two Ca 2+ binding EF-hand domains separated by acidic amino acid rich region and a leucine zipper (Figure 1) (Barnikol-Watanabe et al 1994;Miura et al 1992). Genes encoding NUCB1 and NUCB2 are located in 19q13.2-q13.4 and 11p15.1-p14, respectively, and are deemed to be derived from a common four-domain EF-hand ancestor (Karabinos et al 1996). Within the cell both are located in the cytoplasmic and Golgi luminal pools, both are secreted into extracellular space and interact with other proteins in a calciumdependent manner (Lavoie et al 2002;Lin et al 2000;Morel-Huaux et al 2002;Taniguchi et al 2000;Islam et al 2006).…”
mentioning
confidence: 99%
“…In addition to these motifs/ regions, NEFA has a probable nuclear localization signal, a basic amino acid region sandwiched between the two EF-hands, and a leucine zipper. Because of its extensive similarity to calnuc (61.56% sequence similarity), NEFA was alternately named as Nucb2 (25).…”
Section: Isoforms Of Calnuc and Its Multiple Domainsmentioning
confidence: 99%
“…Phylogenetic analysis revealed that calnuc2 and calnuc have a common four-domain EF-hand ancestor, CTER (25). EF-hand motifs in proteins such as calmodulin and troponin C seem to have evolved from the CTER domains after undergoing a long process of genetic transformation, involving splicing, gene duplication, translocations, genetic fusions, and other similar methods of genetic evolution (25).…”
Section: Isoforms Of Calnuc and Its Multiple Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their complex structure, understanding their diverse functions is an arduous task. Calnuc is one such Ca 2ϩ binding, Golgi-resident protein with multiple domains, highly conserved in species as varied as Ciona intestinalis to Homo sapiens (3)(4)(5)(6). Earlier reports on calnuc conferred it with a DNA binding property (4), and subsequently the presence of other domains was established including EF-hand Ca 2ϩ -binding sites (3), a cyclooxygenase (COX)-binding site (7,8), a G protein-binding site (9), and a species-specific variable C-terminal region.…”
mentioning
confidence: 99%